Real-world solutions for developing high-quality PHP frameworks and applications - Bergmann, Sebastian, 1978-; Priebsch, Stefan (Wrox guides., 2011)
Presents information and a variety of case studies focusing on creating sustainable applications and frameworks using PHP.